Carework and caring: A path to gender equitable practices among men in South Africa? - Jewkes Rachel; Morrell Robert (International Journal for Equity in Health, 2011)
Abstract Background The purpose of this study was to examine the relationship between men who engage in carework and commitment to gender equity. The context of the study was that gender inequitable masculinities create vulnerability for men and women to HIV and other health concerns. Interventions are being developed to work with masculinity and to 'change men'. Researchers now face a challenge of identifying change in men, especially in domains of their lives beyond relations with women. Engagement in carework is one suggested indicator of more gender equitable practice. Methods A qualitative approach was used. 20 men in three South African locations (Durban, Pretoria/Johannesburg, Mthatha) who were identified as engaging in carework were interviewed. The men came from different backgrounds and varied in terms of age, race and socio-economic status. A semi-structured approach was used in the interviews. Results Men were engaged in different forms of carework and their motivations to be involved differed. Some men did carework out of necessity. Poverty, associated with illness in the family and a lack of resources propelled some men into carework. Other men saw carework as part of a commitment to making a better world. 'Care' interpreted as a functional activity was not enough to either create or signify support for gender equity. Only when care had an emotional resonance did it relate to gender equity commitment. Conclusions Engagement in carework precipitated a process of identity and value transformation in some men suggesting that support for carework still deserves to be a goal of interventions to 'change men'. Changing the gender of carework contributes to a more equitable gender division of labour and challenges gender stereotypes. Interventions that promote caring also advance gender equity.